Network pharmacology-based mechanism prediction and pharmacological validation of Xiaoyan Lidan formula on attenuating alpha-naphthylisothiocyanate induced cholestatic hepatic injury in rats. (24th April 2021) - Wang, Meiqi; Liu, Fangle; Yao, Yufeng; Zhang, Qiuyu; Lu, Zenghui; Zhang, Runjing; Liu, Changhui; Lin, Chaozhan; Zhu, Chenchen
Abstract: Ethnopharmacological relevance: The well-known Chinese prescription, Xiaoyan Lidan Formula (XYLDF), possesses efficiency of heat-clearing, dampness-eliminating and jaundice-removing. It has long been used clinically for the treatment of hepatobiliary diseases due to intrahepatic cholestasis (IHC). However, the mechanism of XYLDF for its therapeutic effects remains elusive. Aim of the study: The study aimed to explore the potential targets for liver protective mechanism of XYLDF based on network pharmacology and experimental assays in ANIT-induced cholestatic hepatic injury (CHI) in rats. Materials and methods: On the basis of the 29 serum migrant compounds of XYLDF elucidated by UPLC-TOF-MS/MS, a network pharmacology approach was applied for the mechanism prediction. Systematic networks were constructed to identify potential molecular targets, biological processes, and signaling pathways. And the interactions between significantly potential targets and active compounds were simulated by molecular docking. For the mechanism validation, an ANIT-induced rat model was used to evaluate the effects of XYLDF on CHI according to serum biochemistry, bile flow rates, histopathological examination, and the gene and protein expression including enzymes related to synthesis, export, and import of bile acid in liver and ileum, and those of inflammatory cytokines, analyzed by RT-qPCR and WB. Results: The results of network pharmacology research indicated TNF (TNF-α), RELA (NF-κB), NR1H4 (FXR), and ICAM1 (ICAM-1) to be the important potential targets of XYLDF for cholestatic liver injury, which are related to bile metabolism and NF-κB-mediated inflammatory signaling. And the molecular docking had pre-validated the prediction of network pharmacology, as the core active compounds of XYLDF had shown strong simulation binding affinity with FXR, followed by NF-κB, TNF-α, and ICAM-1. Meanwhile, the effects of XYLDF after oral administration on ANIT-induced CHI in rats exhibited the decreased levels of transaminases (ALT and AST), TBA, and TBIL in serum, raised bile flow rates, and markedly improved hepatic histopathology. Furthermore, consistent to the above targets prediction and molecular docking, XYLDF significantly up-regulated the expression of FXR, SHP, BSEP, and MRP2, and down-regulated CYP7A1 and NTCP in liver, and promoted expression of IBABP and OSTα/β in ileum, suggesting the activation of FXR-mediated pathway referring to bile acid synthesis, transportation, and reabsorption. Moreover, the lower levels of TNF-α in plasma and liver, as well as the reduced hepatic gene and protein expression of NF-κB, TNF-α, and ICAM-1 after XYLDF treatment revealed the suppression of NF-κB-mediated inflammatory signaling pathway, as evidenced by the inhibition of nuclear translocation of NF-κB. Conclusions: XYLDF exhibited an ameliorative liver protective effect on ANIT-induced cholestatic hepatic injury. The present study has confirmed its mechanism as activating the FXR-regulated bile acid pathway and inhibiting inflammation via the NF-κB signaling pathway. Graphical abstract: Image 1 Highlights: The mechanisms of XYLDF for Cholestatic hepatic injury (CHI) were explored. A combined approach of network pharmacology and experimental assay was applied. TNF, NF-κB, FXR, and ICAM-1 were predicted as potential therapeutic targets of XYLDF for CHI. TNF, NF-κB, FXR, and ICAM-1 were predicted as potential therapeutic targets of XYLDF for CHI. FXR-regulated bile acid pathway and NF-κB signaling pathway were associated with the therapeutic mechanism of XYLDF.